Hepatocyte senescence induced by radiation and partial hepatectomy in rat liver. (October 2014) - Serra, Maria Paola; Marongiu, Fabio; Sini, Marcella; Marongiu, Michela; Contini, Antonella; Wolff, Hendrik; Rave-Frank, Margret; Krause, Petra; Laconi, Ezio; Koenig, Sarah
Abstract Purpose: Exposure to radiation primes the liver for extensive replacement of the resident parenchymal cells by transplanted hepatocytes. The mechanisms underlying this repopulation remain to be clarified. In these studies, we examined the possible occurrence of cell senescence in vivo following radiation-associated preconditioning of the host liver. Materials and methods: Fischer 344 rats underwent external-beam, computed-tomography-based partial liver irradiation. A single dose of 25 Gy was delivered to the right liver lobes (40% of liver mass). An additional group of animals received a 1/3 partial hepatectomy (removal of the left anterior lobe) four days after irradiation. Non-irradiated groups served as controls. All rats were sacrificed four weeks after the initial treatment. Results: The irradiated livers displayed several markers of cell senescence, including expression of senescence-associated-β-galactosidase (SA-β-gal), increase in cell size, and up-regulation of cyclin-dependent kinase inhibitors (CDK-I) p16 and p21. Furthermore, quantitative reverse-transcriptase polymerase chain reaction (qRT-PCR) analysis revealed activation of the senescence-associated secretory phenotype (SASP), including the cytokines interleukin 6 (IL6) and 1α (IL1α). The senescence-related changes were more prominent in rats undergoing partial hepatectomy (PH) following irradiation (IR). Conclusions: We conclude that priming with radiation for liver repopulation results in the induction of cell senescence and the up-regulation of a senescence-associated secretory phenotype. The latter can contribute to the extensive growth of transplanted cells in this system.